Identification and Full Genome Analysis of the First Putative Virus of Sea Buckthorn (Hippophae rhamnoides L.) - Balke, Ina; Zeltina, Vilija; Zrelovs, Nikita; Kalnciema, Ieva; Resevica, Gunta; Ludviga, Rebeka; Jansons, Juris; Moročko-Bičevska, Inga; Segliņa, Dalija; Zeltins, Andris (Microorganisms (Basel), 2022)
The agricultural importance of sea buckthorn (SBT; Hippophae rhamnoides L.) is rapidly increasing. Several bacterial and fungal pathogens infecting SBT have been identified and characterized; however, the viral pathogens are not yet known. In this study, we identified, isolated, and sequenced a virus from a wild plantation of SBT for the first time. Sequence analysis of the obtained viral genome revealed high similarity with several viruses belonging to the genus Marafivirus. The genome of the new virus is 6989 nucleotides (nt) in length according to 5′, 3′ RACE (without polyA-tail), with 5′ and 3′ 133 and 109 nt long untranslated regions, respectively. The viral genome encoded two open reading frames (ORFs). ORF1 encoded a polyprotein of 1954 amino acids with the characteristic marafivirus non-structural protein domains—methyltransferase, Salyut domain, papain-like cysteine protease, helicase, and RNA-dependent RNA polymerase. ORF1 was separated from ORF2 by 6 nt, encoding the coat protein (CP) with typical signatures of minor and major forms. Both CP forms were cloned and expressed in a bacterial expression system. Only the major CP was able to self-assemble into 30 nm virus-like particles that resembled the native virus, thus demonstrating that minor CP is not essential for virion assembly.